Recent advances in graphene-derived materials for biomedical waste treatment - Obayomi, Kehinde Shola; Lau, Sie Yon; Mayowa, I.E.; Danquah, M.K.; Jianhua, Z.; Chiong, Tung; Meunier, L.; Rahman, M.M. (2023)
Untreated biomedical wastes discharged into water bodies, primarily by hospitals and health care facilities; release a wide range of contaminants that poses danger to human health and environmental sustainability. Therefore, developing sustainable and dependable treatment methods for biomedical waste is a top priority. Nano-sized graphene is known to have excellent unique properties including high current density, optical, mechanical, thermal conductivity, high chemical stability, high surface area and chemical stability. Graphene-based nanomaterials and derivatives as a result of their excellent properties have received increased attention in wastewater treatment in recent years. Despite significant progress in the production of graphene at laboratory scale, there is a need to focus on green large-scale graphene synthesis to pave the way for adopting graphene-based technology on an industrial scale. In wastewater treatment, advanced development of pure graphene on various significant functionalization exhibits excellent adsorption efficiency when functionalized when compared to other alternatives. Top-down as well as bottom-up approaches such as chemical vapour deposition, and chemical exfoliation among other approaches can be used for graphene synthesis and functionalization. As a result, the benefits of graphene oxide-based nanomaterials have been unraveled in the treatment of biomedical wastewater. Adsorption and photocatalysis techniques have sparked widespread interest because they allow for the environmentally friendly treatment of biomedical wastewater, and significant progress has been made in recent years. This study examined the graphene synthesis method and the use of graphene oxide-based nanomaterials as adsorbents and photocatalysts in the treatment of biomedical waste. Furthermore, the recyclability, thermal stability, and future perspectives on the directions and difficulties in graphene-based material synthesis are summarized.